Numerical Study of Natural Convection in a Ferrofluid-Filled Corrugated Cavity With Internal Heat Generation - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Asme, 2016)
In this paper, numerical simulations for the natural convection in a ferrofluid-filled corrugated cavity with internal heat generation under the influence of a magnetic dipole source were performed. The cavity is heated from below and cooled from above while vertical side walls are assumed to be adiabatic. A magnetic dipole source was located under the bottom heated wall. The governing equations were solved by Galerkin weighted residual finite-element formulation. The influence of external Rayleigh number (between 10(4) and 5 x 10(5)), internal Rayleigh number (between 10(4) and 5 x 10(6)), magnetic dipole strength (between 0 and 4), horizontal (between 0.2 and 0.8) and vertical (between -5 and -2) locations of the magnetic dipole source on fluid flow, and heat transfer are numerically investigated. It was observed that depending on heating mechanism (the external or internal heating), the presence of corrugation of the bottom wall either enhances or deteriorates the absolute value of the averaged heat transfer. The strength and locations of the magnetic dipole source affect the distribution of the flow and thermal patterns within the cavity for both flat and corrugated wall cavity. The net effect of the complicated interaction of the internal heating, external heating, and ferroconvection of magnetic source results in heat transfer enhancement with increasing values of magnetic dipole strength. Wall corrugation causes more enhancement of averaged heat transfer and this is more pronounced for low values of vertical location of magnetic source.
Keywords: Mhd Mixed Convection; Backward-Facing Step; Lid-Driven Cavity; Entropy Generation; Forced-Convection; Nanofluid Flow; Magnetic-Field; Square Cavity; Bottom Wall; Simulation